The Ultimum Remedium Doctrine and The Absolute Obligation to Treat: Constructing A Normative Line of Demarcation in Emergency Department Services - Abu Sufyan; Shinta Ayu Purnamawati; Surya Anoraga; Tongat (KRTHA BHAYANGKARA, 2026)
This study examines the normative tension between the absolute prohibition on refusing emergency patients under the Health Law and the subsidiarity principle of the National Criminal Code, which treats criminal punishment as a measure of last resort (ultimum remedium). The tension arises because the Health Law admits no explicit exception for resource constraints, whereas the Criminal Code requires criminal instruments to be activated only after non-criminal avenues fail, leaving Emergency Department (ED) staff exposed to legal uncertainty amid overload, limited specialists, and equipment shortages. Unlike prior studies examining patient refusal or medical negligence separately, this study’s novelty lies in integrating the ultimum remedium doctrine with the absolute obligation to treat, to construct a normative line of demarcation between criminally actionable refusal and medically justifiable delay. The study uses an empirical juridical method combining statutory, conceptual, historical, and socio-legal approaches; primary data were obtained through in-depth interviews, observation, and documentation involving six informants at a Type B hospital in Banyuwangi, analyzed using an interactive model. Findings show that delays attributable to triage, overload, facility limitations, and documented referral procedures do not constitute criminally actionable refusal; criminal prosecution is warranted only where there is demonstrable intent, gross negligence, or disregard for patient safety without valid medical grounds. Accordingly, this study formulates a normative line of demarcation based on six assessment parameters: the presence of initial emergency care, the mens rea element, the medical and procedural basis, completeness of documentation, a proportionate legal response, and the relevant normative foundation.